PENGELOLAAN LIMBAH MEDIS PADAT DI RSUD KOTA DUMAI TAHUN 2023 - Herawati Sipayung, Tetti; Dewi, Oktavia (Ensiklopedia of Journal, 2024)
Introduction: Dumai City Hospital produces liquid waste, solid medical waste, non-medical waste and gas waste. Health facilities (hospitals and community health centers) in Indonesia that manage medical waste according to standards are 18.9%. Riau Province, of 215 health service facilities including hospitals and community health centers, only 27 (6.9%) health service facilities have managed medical waste in accordance with standards (Ministry of Health, 2021). The aim of this research is to determine the management of solid medical waste in City Hospitals. Dumai 2023. The research method used descriptive qualitative, there were 6 informants consisting of the Head of the Kesling Installation, Head of Room, Medical Waste Transport Staff, Medical Waste Management Staff, K3RS Staff and Nurses. Data were collected using interview methods, document searches and field observations. Research results: Dumai City Hospital produces an average of 150 kg of solid medical waste every day. The type of solid medical waste produced is infectious medical waste such as bandages, syringes, gloves and pharmaceutical waste. In the process of destroying solid medical waste, hospitals carry out destruction using an incinerator which is done once a day every day. This hospital also collaborates with a licensed waste transport company. Conclusion: The management of solid medical waste at the Dumai City Regional General Hospital does not meet the requirements according to Minister of Health Regulation Number 2 of 2023, this is because the temporary waste disposal site does not comply with the regulations. Suggestion: The need for cooperation from all parties in the successful management of Medical Waste, the need to increase HR competency in managing Solid Medical Waste.Keywords: Hospital solid medical waste, facilities and infrastructure